Economy and ethics in the development of the Italian health-care system - Bompiani, Adriano (Medicina e Morale, 1996)
In Italy, as in the industrialized countries of Western Europe, there have been considerable demographic and epidemiological changes (aging of the population and an increase in number of the elderly, reduction of infective pathologies and an increase of degenerative diseases), associated with important social phenomena (voluntary reduction of fertility, progressive increase of non domestic work by women). At the same time the capacity to treat acute diseases has increased, technology is developing unceasingly and there is an increasing request for "being healthy" as the individual's right. This has led to the conception of new health structures, while the "Welfare State" has disappeared and the strategy of promoting health through prevention has not yet been very successful. Starting from these difficulties and with the awareness of the ethical importance of these problems, since the extension of the right to the health service for all citizens is unquestionable, the article examines the relationships between the principle of justice, basically translated by the principle of equity, and the health economy. Moreover, within the various questions dealt with (the health service in general, the purchase of resources for the health service in Italy and in the other European countries, the proposal for so-called federalism in the health service, the use of resources and the economic rationalization of expenses) the ethical and bioethical implications regarding the various currents of thought, that is, utilitarianism, liberatarian individualism, equalitarianism and personalism, have also been pointed out.